Efektifitas Pembelajaran Berbasis PJBL (Project Basic Learning) Terhadap Motivasi dan Hasil Belajar Pada Mata Kuliah Eletronika Analog dan Digital - Suhaeb, Sutarsi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The objectives of this Study are (1) to find out how the Effectiveness of Using PJBL (Project basic learning) on Motivation in digital analogue Electronics course. (2) to know how the effectiveness of using PJBL on Learning Outcomes in analog and Digital electronics courses. Method The research used was using a quantitative pseudo-experiment (quasi-experiment) approach with a nonequivalent control group design. This design was used to compare the effectiveness of the PJBL model on students’ motivation and learning outcomes in Analog and Digital Electronics courses between experimental and control classes. Based on the results of the study it can be concluded that Based on the results of the study it can be concluded that : (1) Hypothesis Test (Independent t Test) was obtained result Value t = 6.303 with Value p = 3.40 × 10⁻⁸ 0.05. That is, there was a highly statistically significant difference between the learning motivation of students using the PJBL model and students using conventional learning. So that the Effectiveness of Using PJBL (Project basic learning) against Motivation in the course Digital analogue electronics four motivates students to learn, (2) Hypothesis Test (Independent t Test) obtained results Value t = 4.89 and Value p = 0.000where5 value is significant) then Karest (highly statistically significant difference between the learning outcomes of students who followed learning with PJBL and conventional learning so that it can be concluded Effectiveness of Using PJBL (Project basic learning) against Learning outcomes on the course Digital analog electronics effectiveness and improved learning outcomes.